Acessibilidade a hospitais - Garcia, Patrícia Baldini de Medeiros (Universidade Federal de São Carlos, 2012)
Developments in the health sector, especially those placed in public care are fundamental to the care of the entire population of a city and region. The location of health projects such as "Santa Casa" was made since many decades ago, or even the latest developments seem not to have been concerned with the accessibility of the population. Moreover, the travels generators poles, including the establishments of the health sector, cause significant impacts on its surroundings and also in the transport systems of the region they live. In general, the public hospitals, mainly in Brazil, aim to attend the portions of the population of low income families that use displacement on foot, by car or public transport. As a result, this study aimed to perform an analysis of levels of accessibility to hospitals such as "Santa Casa", considering mainly the population groups that most need the public health. The proposed method is based on an indicator (time) to measure accessibility to hospitals by different ways: on foot, by car and public transport, making use of geographic information systems. IBGE data were used to estimate the income levels of traffic areas. A survey with users from hospitals located in the cities of Rio Claro and São Carlos was performed to characterize the source and location of the travel. Using the data obtained in both case studies it was found that the population, in most cases, has used the car travel to hospitals. The accessibility by car was high, because even in distant neighborhoods, the travel time was at 15 minutes for both cities. In contrast, traveling on foot had low accessibility in relation to hospitals, mainly in the distant neighborhoods. The analysis done for public transport accessibility shows the minimum value of 30 minutes to Rio Claro and 35 minutes to São Carlos. Analyzing data from the 2000 Census, it is evident that the population with lower monthly household income is concentrated in the suburb areas of the cities. Thus, the distances done every day by the citizens compromise the access to different services available in the cities, as the travel time, or the lack of public transport routes, or lack of conditions of using public transport.
Keywords: Acessibilidade; Pólos geradores de viagens; Hospitais; Accessibility; Trip generation poles; Hospitals; ENGENHARIAS